2010
DOI: 10.1007/s00418-010-0681-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolucytotic gold ions on recovering brain lesions

Abstract: Recent experimental research has shown that metallic gold releases charged gold atoms when placed intracerebrally and that the liberated gold ions affect inflammation in the brain. The observations suggest that metallic gold can be used as a safe suppressor of inflammation in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Since gold in the Swarna bhasma is approximately 28–35 nm in size, it can reach the affected site on oral administration via intestinal absorption and possibly can release Au(I) ions in a sustained manner required for therapeutic action. [42] These results reinforce the application of Swarna bhasma as a therapeutic agent in clinical medicine from the safety point of view. These testing protocols may be adopted as a screening test for all bhasma preparations to meet the criteria that supports its use worldwide.…”
Section: Resultssupporting
confidence: 65%
“…Since gold in the Swarna bhasma is approximately 28–35 nm in size, it can reach the affected site on oral administration via intestinal absorption and possibly can release Au(I) ions in a sustained manner required for therapeutic action. [42] These results reinforce the application of Swarna bhasma as a therapeutic agent in clinical medicine from the safety point of view. These testing protocols may be adopted as a screening test for all bhasma preparations to meet the criteria that supports its use worldwide.…”
Section: Resultssupporting
confidence: 65%
“…The results also allow a better understanding of the activity of gold implants: Danscher [29] and Danscher and Larsen [30] have shown that gold ions are liberated from gold implants, and that is now, on the basis of our studies, understandable as dissolution of active gold sites by free oxygen radicals which are typically formed in immune defense reactions.…”
Section: The Electrochemical Deposition Of Pt On Polycrystallinementioning
confidence: 82%
“…However, gold ions, dissolucytotically released from metallic gold implants, have been shown to be anti-inflammatory [18,23-26]. Together with recent findings of decreased articular pain and inflammation in veterinary use [6,8], it is of interest to analyse the mode of action of metallic gold which can be applied to specific points of inflammation without systemic effects.…”
Section: Discussionmentioning
confidence: 99%